ANALISA VEGETASI HUTAN RIPARIAN DATARAN RENDAH DITEPI SUNGAI NGGENG, TAMAN NASIONAL KAYAN MENTARANG, KALIMANTAN TIMUR - Purwaningsih, Purwaningsih (Research Center for Biology-Indonesian Institute of Sciences, 2009)
Study on the riparian forest of Nggeng River bank at Kayan Mentarang National Park was carried out with quadrate method. It would cover species composition and vegetation structure. The results of a floristic inventory of trees with DBH e